Transformational leadership contributions for employee autonomy - Dias, Á.; Pascoal, B.; Pereira, L.; Lopes da Costa, R. (International Journal of Service Science, Management, Engineering, and Technology, 2022)
The performance of a company is affected by several variables and understanding them and knowing how they work is decisive for management. Therefore, this research aims to address and measure how transformational leadership impacts the employees work. To test the conceptual model, we used survey data from 174 active workers. Data was analyzed using PLS-SEM. Our results reveal that leaders who adopt a Transformational approach allow workers to be more autonomous in their work, the autonomy leverage the existence of efficiency in tasks and processes. Efficiency is also reached through cost savings, which translates into a reduction of unproductive work time. Furthermore, results indicate the mediating effect of efficiency and employee autonomy on the relation between transformational leadership and cost savings and between transformational leadership and unproductive work time.